Analysis Of Lexical Semantic Ambiguity In Translating Indonesian Sentences Into English Using Google Translate And Chat-GPT - Lumban Gaol, Daniel Binsah; Anggita Ristia Damanik, Bernieke (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
The background of this study focuses on the importance of accuracy in translating sentences containing lexical ambiguity. Misunderstandings often occur in cross-language understanding because each language must have a translation tool by selecting and translating sentences with many possible meanings. This study aims to analyze the results of translating Indonesian sentences containing lexical ambiguity into English using two translation engines, namely Google Translate and ChatGPT. The method used is descriptive qualitative with a content analysis approach. Data in the form of sentences containing ambiguity were collected and translated using both tools, then analyzed based on semantic theory and translation theory. The results of the study show that both translation tools are able to translate ambiguous sentences with varying degrees of success. The results of the analysis show that both Google Translate and ChatGPT have the ability to translate sentences where there is a meaning with varying degrees of success. ChatGPT tends to produce translations that are more contextual and closer to the actual meaning than Google Translate which tends to translate literally. Thus, it can be concluded that the development of translation technology must consider the ability to understand context semantically so that the translation results are more accurate and natural.